Anthrax toxin receptor drives protective antigen oligomerization and stabilizes the heptameric and octameric oligomer by a similar mechanism. - Alexander F Kintzer; Harry J Sterling; Iok I Tang; Evan R Williams; Bryan A Krantz (PLoS ONE)
Background Anthrax toxin is comprised of protective antigen (PA), lethal factor (LF), and edema factor (EF). These proteins are individually nontoxic; however, when PA assembles with LF and EF, it produces lethal toxin and edema toxin, respectively. Assembly occurs either on cell surfaces or in plasma. In each milieu, PA assembles into a mixture of heptameric and octameric complexes that bind LF and EF. While octameric PA is the predominant form identified in plasma under physiological conditions (pH 7.4, 37°C), heptameric PA is more prevalent on cell surfaces. The difference between these two environments is that the anthrax toxin receptor (ANTXR) binds to PA on cell surfaces. It is known that the extracellular ANTXR domain serves to stabilize toxin complexes containing the PA heptamer by preventing premature PA channel formation--a process that inactivates the toxin. The role of ANTXR in PA oligomerization and in the stabilization of toxin complexes containing octameric PA are not understood. Methodology Using a fluorescence assembly assay, we show that the extracellular ANTXR domain drives PA oligomerization. Moreover, a dimeric ANTXR construct increases the extent of and accelerates the rate of PA assembly relative to a monomeric ANTXR construct. Mass spectrometry analysis shows that heptameric and octameric PA oligomers bind a full stoichiometric complement of ANTXR domains. Electron microscopy and circular dichroism studies reveal that the two different PA oligomers are equally stabilized by ANTXR interactions. Conclusions We propose that PA oligomerization is driven by dimeric ANTXR complexes on cell surfaces. Through their interaction with the ANTXR, toxin complexes containing heptameric and octameric PA oligomers are similarly stabilized. Considering both the relative instability of the PA heptamer and extracellular assembly pathway identified in plasma, we propose a means to regulate the development of toxin gradients around sites of infection during anthrax pathogenesis.